Performance of Polymer Composite Constituted Cabinet Dryer Integrated within a Solar Flat Plate Collector - S. Raj Sachin; Anton M. Kuzmin; Subramanian Krishnakumar; Anandhan Jayaganthan; Yesgat Admassu (Advances in Materials Science and Engineering)
Generally, solar dryer cabinets are made up of sheet metals that are heavy, costly, tend to rust over time, and possess the high heat rate to the outer atmosphere. In order to overcome these drawbacks, this research urges to develop a natural fiber reinforced polymer-based cabinet dryer, specially designed and fabricated for the purpose of solar drying. Nylon is used as the matrix material and Prosopis juliflora in particulate form is used as the natural fiber reinforcement. The dryer cabinet was designed at industrial scale to dry 5 kg of ginger at a single setting. This work also studies the efficiency of the polymer composite cabinet integrated with a flat plate solar collector system that is coated with copper and black chrome attached to corrugated fins in between the absorber plate and storage medium. The FRP chamber was compartmented in its interior with aluminium perforated sheets and experimentation was performed to determine the efficiency of the composite cabinet based on reduction of heat loss from the system. The performance of the coating, storage medium materials, and overall storage efficiency were also studied. The FRP cabinet resulted in a moisture level less than 8.5% within 4–7 days. Exergy studies showed 75% efficiency and energy studies gave 25.5 kJ/kg peak readings of drying efficiency for a period ranging between 11 and 12 hours. This was a 75% increment in energy efficiency. Thermal degradation of the FRP material was found to be stable up to 300°C. The overall weight of the constructed polymer cabinet was 25% lesser than the conventional systems.